A munkaerő-migráció változása a kétezres években Magyarországon: Vizsgálat a munkaerő-felmérés adatai alapján - Hárs Ágnes; Simon Dávid (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
– Emigration has accelerated since 2007 in Hungary. The short history of the new phenomenon called intense political and social reactions. The paper focuses on a particular segment of emigration: on labour emigration of those employed persons who are still connected to the home country and possible to the Hungarian labour market. Based on the Hungarian LFS data those employed persons will be covered who reported that their workplace has been abroad. Since the early 2000s until the first quarter of 2013 has been followed the changing trend, orientation and structural characteristics of labour emigration. The trend and the explanatory factors of changing emigration will be discussed by main target countries. Finally the individual's chance of emigration and its changes comparing to the employed population in the home country has been studied by logistic regression analysis. The odds ratio and the changes of the odds ratio of labour emigration calculated by main target countries proves considerable structural rearrangement over time and characteristic differences by main target countries.
Keywords: F22; J21; J60; 330; migration; working abroad; employment; labour market